2003
DOI: 10.1046/j.1365-2958.2003.03535.x
|View full text |Cite
|
Sign up to set email alerts
|

Global regulation by CsrA in Salmonella typhimurium

Abstract: SummaryCsrA is a regulator of invasion genes in Salmonella enterica serovar Typhimurium. To investigate the wider role of CsrA in gene regulation, we compared the expression of Salmonella genes in a csrA mutant with those in the wild type using a DNA microarray. As expected, we found that expression of Salmonella pathogenicity island 1 (SPI-1) invasion genes was greatly reduced in the csrA mutant, as were genes outside the island that encode proteins translocated into eukaryotic cells by the SPI-1 type III sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
199
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(215 citation statements)
references
References 57 publications
(94 reference statements)
15
199
0
1
Order By: Relevance
“…The study demonstrated alterations in global regulator, PNPase as a key element of virulence and persistency of Salmonella. The role of another global regulator, csrA in virulence of S. enterica Typhimurium was found in a similar study [59]. Recent analyses of gene expression of double murein lipoprotein mutant of the pathogen revealed alterations in the expression of flagellar, invasion, and virulence gene regulators in the mutant compared to the parent strain.…”
Section: Pathogenesissupporting
confidence: 61%
“…The study demonstrated alterations in global regulator, PNPase as a key element of virulence and persistency of Salmonella. The role of another global regulator, csrA in virulence of S. enterica Typhimurium was found in a similar study [59]. Recent analyses of gene expression of double murein lipoprotein mutant of the pathogen revealed alterations in the expression of flagellar, invasion, and virulence gene regulators in the mutant compared to the parent strain.…”
Section: Pathogenesissupporting
confidence: 61%
“…Since the effects of CsrA homologs in other eubacterial species have been shown to be antagonized via interactions with multiple binding sites present on noncoding small RNA molecules such as CsrB and CsrC, we hypothesized that the effects of CsrA in borrelial strains could be subjected to such regulatory effects by small RNA homologs (6,46). Bioinformatic approaches to identify the small RNA molecule(s) that could titrate the effects of CsrA have not yielded sequences with significant homology to CsrB/CsrC, while a homolog of small RNA molecule DsrA Bb has been determined to mediate the temperature-induced regulation of RpoS (50).…”
Section: Discussionmentioning
confidence: 99%
“…Mutation of CsrA in these organisms has dramatic and highly pleiotropic defects in carbon metabolism, quorum sensing, biofilm formation, and motility (17)(18)(19)(20). CsrA-deficient bacterial pathogens are typically attenuated for virulence, which is likely a result of misregulation of target gene expression and the resulting inability to make critical physiological transitions during an infection (1,(21)(22)(23).…”
mentioning
confidence: 99%